2017
DOI: 10.1016/j.jcmg.2017.02.005
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic CT Methodology for the Evaluation of Subclinical Leaflet Thrombosis

Abstract: Subclinical leaflet thrombosis was recently described in a randomized trial of transcatheter aortic valve replacement. It was subsequently demonstrated in a series of registries that this was a commonly observed imaging finding seen in all transcatheter and surgical bioprostheses. The phenomenon has aroused considerable interest due to the as-yet-undefined risk for later clinical events and the possibility of pharmacological intervention with anticoagulation. Subclinical leaflet thrombosis is easily detected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 6 publications
0
97
0
2
Order By: Relevance
“…Fundamentally, we need to establish CT diagnostic criteria for valve thrombosis and its severity. Recently reported systematic CT methodology for the evaluation of subclinical leaflet thrombosis devised during the Portico trial investigation may be useful 30. Echocardiography is non-invasive and permits repeated use, thus being suitable for follow-up.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…Fundamentally, we need to establish CT diagnostic criteria for valve thrombosis and its severity. Recently reported systematic CT methodology for the evaluation of subclinical leaflet thrombosis devised during the Portico trial investigation may be useful 30. Echocardiography is non-invasive and permits repeated use, thus being suitable for follow-up.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…7 Though some studies have shown higher longterm survival rates in patients with increased surgical risk who undergo TAVR versus surgery, 4 complications including subclinical thrombus formation, paravalvular leakage, prosthesis migration/embolization, stroke, permanent pacemaker, and coronary occlusion have motivated numerous in vitro and in silico studies to provide greater understanding and improve clinical practice. [8][9][10][11][12][13][14][15][16] To facilitate further research and investigation into the hemodynamic profiles of the post-TAVR aortic root, a greater understanding of how aortic root geometry changes after TAVR is imperative. Current research utilizes a heterogeneous mix of aortic root geometries of healthy patients, untreated AS patients and patients that have been indicated for TAVR.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum velocity is 4.9 cm/s that indicates severe aortic stenosis while on warfarin during the readmission with respiratory failure. Rivaroxaban for the prevention of major cardiovascular events after transcatheter aortic valve replacement: rationale and design of the GALILEO study TTE 1,520 Pending Pending Collet et al [5] Anti-thrombotic strategy after trans-aortic valve implantation for aortic stenosis (ATLANTIS) TBD 1,510 Pending Pending nosed by cardiac CT as hypoattenuated leaflet thickening associated with reduced leaflet motion [1]. There is a discrepancy in the incidence of TAVR thrombosis detected by TTE versus CT imaging, with CT being more sensitive.…”
Section: Discussionmentioning
confidence: 99%